Effects of oxygen concentration on microbial growth in aerated palm oil mill effluent using oxygen enriched air membrane system - Mohd. Tajuddin, Ramlah; Ismail, Ahmad Fauzi; Salim, Mohd. Razman (2004)
Aeration is one of the most important factors in biological wastewater treatment process. Through aeration, oxygen is supplied to the bacteria to allow their respiration to proceed rapidly and satisfy the biochemical oxygen demand (BOD). This study was carried out to determine the biological growth in aerated palm oil mill effluent (POME) when subjected to aeration using air of different oxygen concentration. Pure oxygen (101% O2), diffused air (20.9% O2 ), and oxygen-enriched air (26.7% O2 ) were used to aerate the POME for three weeks continuously at a flow rate of 0.1 LPM. Oxygen enriched air was supplied by an oxygen enriched air system (OEAS). This system is able to enriched oxygen concentration of air up to 26.7% using membrane with composition consisting of 22% polysulfone, 31.8% dimethylacitemide, and 14.4% ethanol. Samples subjected to aeration with air of three different oxygen concentration were tested for several water quality parameters which include pH, temperature, BOD, chemical oxygen demand (COD), dissolved oxygen (DO), total solid (TS), total suspended solid (TSS), bacterial count, saturated dissolved oxygen (SDO) and dissolved oxygen deficit for every two days. It was found that bacteria count and BOD reduction in POME when aerated by OEAS was 13.8% and 18.3% respectively more than when it was aerated by diffused air. This shows that an increased in oxygen concentration during aeration can speed up the microbial growth and thus shortened the period of aerobic digestion process.